COMPARATIVE ANALYSIS OF THE NICOTINE EXTRACTION PROCESS FROM NICOTIANA TABACUM L. IN SUPERCRITICAL CONDITIONS UNDER VARIOUS EXTRACTANT FLOWS - Ikhsanov Yerbol Saginovich; Shechenko Anastasiya Sergeevna; Andasova Nazumgul Talgatovna; Nauryzbaev Michael Kasymovich (Academic Scientific Journal of Chemistry, 2020)
In this paper, we present a comparative analysis of various methods and conditions for extraction from the plant Nicotiana tabacum L., harvested in the Almaty region of the Republic of Kazakhstan in 2019. Extraction was carried out at various temperatures at during the extraction process while maintaining pressure in the system 120 bar and a flow of 100 ml/min and 4000 ml/min with the subsequent development of the technology for producing nicotinic acid by oxidation in an aqueous medium. The supercritical extraction method was carried out on a CO2 extraction unit under the following conditions: the temperature range in the reactor 40-80 °C, the pressure 120 bar, a gas flow of 100 ml / min. Extraction was also carried out on the installation which was developed jointly with LLC «Superhydrophobic Coatings» (Nizhny Tagil, Russia) at similar temperatures and pressure but with a 40-fold increase in flow (4000 ml/min). The obtained extracts were studied on a gas chromatograph with a mass selective detector Agilent Technologies 7890N / 5973N GС / MS. Data processing included determining retention times, peak areas and processing of spectral information obtained by using a mass spectrometric detector. The libraries Wiley 7th edition and NIST’02 were used for evaluation of mass spectra. As a result, an almost two-fold increase in the efficiency of the extraction process was achieved while maintaining the previous parameters. In addition, the maximum selectivity of the process is achieved at 120 bar and a temperature 70 ºC. The nicotine content in the final extract increased significantly with reducing the quantitative and qualitative content of impurities which are represented in most higher hydrocarbons and alcohols, which do not have special biological activity and, as a consequence, do not affect the quality of the final product. Our comparative analysis with previously published data shows that a temperature change significantly increases the selectivity of the extraction process, while the highest nicotine content was noted in the extract obtained at 70 ºС. Also under these conditions the smallest impurity content was noted. In addition, only 3,7,11,15- Tetramethyl-2-hexadecen-1-ol (11.31%) and Tetratetracontane (4.70%) were identified in the extract with nicotine. Natural nicotine is in demand in the production of alternative methods of tobacco consumption, such as ecigarette. Nicotine can also be potentially used in medicine as an anesthetic and in the treatment of Alzheimer’s disease. In addition, nicotine is used as an insecticide to protect plants. For these purposes, nicotine was used in the form of a pure substance, its sulfate, tobacco dust, and the pure substance was the most active.